Influence of grinding parameters on surface temperature and burn behaviors of grinding rail. (June 2018) - Lin, B.; Zhou, K.; Guo, J.; Liu, Q.Y.; Wang, W.J.
Abstract: Reasonable grinding parameters are significant problem affecting surface quality of rail grinding. The objective of this study is to explore the effect of grinding parameters on rail grinding temperature and burn behaviors using an inserted semi-artificial thermocouple method. When the grinding temperature exceeds 600 °C, the grinding burn occurs on the rail surface and accompanies with the appearance of white etching layer (WEL). The essence of rail grinding burn is that the rise of grinding temperature causes the aggravation of surface oxidation and the accumulation of nonferrous oxides. When the temperature continuously ascends to 802 °C, visible grinding cracks and quenching cracks are observed. Furthermore, the relationship of surface state, grinding burn and grinding temperature of rail specimen is proposed. Highlights: An inserted semi-artificial thermocouple method was designed and used to evaluate the evolution of grinding temperature. The essence of rail grinding burn is revealed. The relationship between surface state, grinding burn and grinding temperature is proposed. The initiation mechanism of grinding crack and quenching crack is clarified.